PET2015UZ: Prognostic value of pre-treatment 18FDG-PET in operable breast cancer v1 - Vincent Vinh-Hung; Hendrik Everaert; Mark De Ridder (2020)
This retrospective-observational study hypothesizes that preoperative 18FDG-PET for breast cancer has significant prognostic value for the prediction of survival. Data from patients who had breast surgery and had a preoperative FDG-PET examination at the UZ Brussel in 2002-2008 and in 2009-2015 will be analyzed without restriction on age or sex. Data collection for the cohort 2002-2008 has been finalized and will be shared on Mendeley (Reserved DOI: 10.17632/sfvtmrd8z9.1 ). Data for the cohort 2009-2015 will be collected by end of 2020. Detailed and referred to in: # Breast cancer preoperative 18FDG-PET, overall survival prognostic separation compared with the lymph node ratio. # Vinh-Hung V, Everaert H, Gorobets O, Van Parijs H, Verfaillie G, Vanhoeij M, Storme G, Fontaine C, Lamote J, Perrin J, Farid K, Nguyen NP, Verschraegen C, De Ridder M. # Breast Cancer. 2021 Jul;28(4):956-968. doi: 10.1007/s12282-021-01234-z # PMID: 33689151 https://link.springer.com/article/10.1007%2Fs12282-021-01234-z # Is there a utility of [18F]FDG-PET before surgery in breast cancer? A 15-years overall survival analysis. # Perrin, Farid K, Van Parijs H, Gorobets O, Vinh-Hung V, Nguyen NP, Djassemi N, De Ridder M, Everaert H. # World J Clin Oncol. Pending. Study registration: https://www.isrctn.com/ISRCTN17962845